STRATEGI PEMANFAATAN KOTORAN SAPI - Hermain Teguh Prayitno (Badan Perencanaan Pembangunan Daerah (BAPPEDA) Kabupaten Pati, 2018)
ENGLISHCow feces abundant in the pati district. In the theory, anaerobic organic matter change into inorganic produce energy. Meanwhile, scarcity and rising prices of LPG and chemical fertilizers are common, due to the disparity subsidized and non-subsidized price. Purpose of the study is to know the strategy of utilization cow faces, with descriptive quantitative method and SWOT analysis. Internal factors and external factors assessed by the results of 2.38 and 2.92, the positioning strategy of growth through horizontal integration and stability that is intensified and innovation process of making biogas, liquid manure, solid manure becomes easier, cheaper and can be emulated to provide own needs, and towards the avaibility of farmers to face post-subsidy removal. INDONESIAKotoran sapi berlimpah di kabupaten pati. Dalam teori, perubahan anaerob bahan organik menjadi anorganik menghasilkan energi. Sementara, kelangkaan dan peningkatan harga LPG dan pupuk kimia sering terjadi, akibat adanya disparitas harga subsidi dan non subsidi. Tujuan penelitian ingin mengetahui strategi pemanfaatan kotoran sapi, dengan metode deskriptif kuantitatif dan analisis SWOT. Faktor internal dan faktor eksternal dinilai dengan hasil 2,38 dan 2,92 pada posisi strategi pertumbuhan melalui integrasi horisontal dan stabilitas yaitu menggiatkan dan menginovasi proses pembuatan biogas, pupuk cair, pupuk padat menjadi lebih mudah, murah dan dapat ditiru untuk mencukupi kebutuhan sendiri, dan menuju ketahanan peternak dan petani menghadapi paska pencabutan subsidi.